Pet L.O.V.E (Life Of Virtual Entrust): article / Nor Atlina Ismail - Ismail, Nor Atlina (2013)
Pet L.O.V.E (Life of virtual Entrust) is a technology that design for pet to solve human problems with pet manure and litter. Trust no one but technology to take care of pet.Pet L.O.V.E (Life of virtual Entrust) is giving hope to everyone to eliminate the burden of cat litter disposal and at the same time save the nature from the harmful kitty litter killer, Toxoplasma gondii (1). Pet L.O.V.E is semi automatic toilets used an Arduinouno as a microcontroller and the heart of this project is Arduino GSM Shield that use to send Short Message Service (SMS) to the owner when the level of litter reach the limit and when the temperature is too high. This project uses moisture sensor to check the moisture of cat litter and ultrasonic sensor to detect the level of sand in the tank. Servo motor will rotate 360 degree when moisture sensor detects the feces and new sand will insert to replace the use one. Temperature sensor also used in order to detect the changing of temperature for worm. Worm is use in this project to convert the pet feces into the useful worm casting and a liquid fertilizer that can be used on the garden. Using worm is one of the ways to eliminate toxoplasma gondii in pet litter and reduce the risk of contracting this disease.